Long-Term Trends of Coagulation Parameters in People Living With HIV Treated With Combined Antiretroviral Therapy - Bhoelan, Soerajja; Borjas Howard, Jaime; Tichelaar, Vladimir; Bierman, Wouter; Meijer, Karina (Clinical and applied thrombosis/hemostasis, 2023)
Trends of coagulation parameters during long-term treatment with combination antiretroviral therapy (cART) are unclear. We followed 40 male subjects living with human immunodeficiency virus (HIV). Plasma levels of procoagulant parameters, factor VIII, von Willebrand factor and D-dimer, and anticoagulant parameter Protein S (PS), were measured before start and 3 months, 1 year, and 9 years after. Analyses were adjusted for cardiovascular risk factors (age, smoking, and hypertension) at baseline. At baseline, procoagulant parameters were markedly elevated and PS was in the lower range of normal. CD4/CD8-ratio improved during the complete follow-up period. In the first year, procoagulant parameters were decreasing, but at year 9 an increase was observed. After correction for cardiovascular risk factors, this increase was no longer present. PS remained stable during the first year and slightly increased from one to 9 years. This study indicates that decreasing immune activation by cART reverses the procoagulant state in HIV partially during the first year. These parameters increase in the long term despite an on-going decrease in immune activation. This increase might be related to established cardiovascular risk factors.